Diversity and abundance of Ichthyoplankton in Marudu Bay, Sabah, Malaysia - Rezagholinejad, Sadaf (2015)
Larval fish composition, spatio-temporal distribution, density, family richness, evenness and Shannon-Wiener index were determined by analyzing samples collected from the estuarine area of Marudu Bay, Sabah,Malaysia between October 2012 and September 2013. Five sampling stations were selected for the study. Each sampling station was approximately 1 km apart from each other. Monthly sampling was conducted at high tide during new moon period in daylight. Samples of fish larvae were collected using plankton net (350μm) through 20 min subsurface towing in each station. A flowmeter (Hydro-Bios) was attached to the net in order to determine the volume of the water filtered. In total 20 families of fish larvae belonging to 7 orders were identified from the estuarine ecosystem of Marudu Bay, Sabah, Malaysia. A total of 3879 larval fishes were obtained from the estuarine area of Marudu Bay, Sabah, Malaysia. In total, 20 fish larvae families were identified with a mean abundance of 118.43 larvae per 100 m3. Among them, 13 occurred in St-1, 16 in St-2, 17 in St-3, 12 in St-4 and 16 in St-5. Overall four families including Sillaginidae (44%), Engraulidae (14%), Mugilidae (12%) and Sparidae (10%) were the dominant in the study area. Sillaginidae was the most abundant family during the study period which was followed by Engraulidae,Mugilidae and Sparidae. The highest abundance of Sillaginidae was recorded in the month of October. Shannon Wiener index varied significantly different among the months and stations (p < 0.05). The highest mean density (294 individuals/100 m3) of fish larvae was recorded in December at St-4. Water quality parameters recorded were significantly different (p < 0.05) among the five stations except DO and pH (p > 0.05). It is found that five families (Engrualidae, Gobiidae, Mugilidae, Sparidae and Sillaginidae) were negatively and significantly correlated with temperature (p < 0.01). Sillaginidae (r = 0.38) showed significant (p < 0.01) positive correlation with salinity while it was negatively and significantly correlated with Centriscidae (p < 0.01). It was found that the five families (Engrualidae, Gobiidae, Mugilidae, Sparidae and Scatophagidae) were significantly correlated with salinity (p < 0.05). Centriscidae and Mugilidae were significantly correlated with dissolved oxygen (p < 0.01). However it was negatively correlated with Clupeidae (p < 0.05). Positive and highly significant correlations were found between pH and four families that included Clupeidae (r = 0.34, p < 0.01), Gobiidae (r = 0.41, p < 0.01), Mugilidae (r = 0.67, p < 0.01) and Sillaginidae (r = 0.49, p < 0.01). It was also shown that pH had a positive and significant correlation (p < 0.05) with four families (Platycephalidae, Engrualidae, Sparidae and Syngnathidae). Conductivity showed a negative and significant correlation with only Centriscidae (p < 0.01). The highest and most significant regression coefficient (R² = 0.52, p < 0.05) was seen in family Mugilidae where 52% of its abundance were influenced by water quality parameters.